(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A quantitative assessment of antimicrobial activities was carried out by determining the minimum inhibitory and microbicidal concentrations (MICs and MMCs) of the various solvent extracts like 70% ethanol, water , ethyl acetate and chloroform against two Gram negative bacteria - Escherichia coli and Pseudomonas aeruginosa and two Gram positive bacteria - Staphylococcus aureus and Bacillus cereus,. The testing was done by the Agar disc diffusion method. Zones of inhibition of extracts were compared with that of standard ofloxin and amoxicillin antibiotics for antibacterial activity. From our study, we can conclude that ethanol extract has more prevailing and sustainable antibiotic properties than other solvents extract. Preliminary phytochemical screening of Bixa Orellana showed the presence of alkaloids, glycosides, steroids, phenols, tannins, flavonoids and saponins in the crude drug.